2022
DOI: 10.1515/reveh-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Association between food additives and prevalence of allergic reactions in children: a systematic review

Abstract: Food additives contain synthetic and natural chemical compounds and are one of the causes of food allergies. In this regard, it is necessary to recognize the food additives that are of special interest for children. In this survey, the relation between food additives and allergic reactions and attention-deficit hyperactivity disorders in children was studied. The research studies with keywords “allergic reactions”, “hypersensitivity”, “food additives” and “children” were searched in PubMed, Scopus, Science Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The use of food preservatives is one of the effective measures to inhibit the multiplication of microorganisms; however, in recent years, it has been reported that long-term excessive use of chemical preservatives caused adverse health effects. 4,5 Therefore, the research focus has shifted from chemical to natural preservatives.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of food preservatives is one of the effective measures to inhibit the multiplication of microorganisms; however, in recent years, it has been reported that long-term excessive use of chemical preservatives caused adverse health effects. 4,5 Therefore, the research focus has shifted from chemical to natural preservatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gram-negative bacteria such as Escherichia coli, Shigella sonnei, Pseudomonas aeruginosa, Salmonella typhimurium, and Salmonella enteritidis are leading causes of food spoilage and foodborne diseases. , Approximately, 70% of bacterial foodborne diseases are caused by Gram-negative bacteria, posing a great threat to food safety and human health. The use of food preservatives is one of the effective measures to inhibit the multiplication of microorganisms; however, in recent years, it has been reported that long-term excessive use of chemical preservatives caused adverse health effects. , Therefore, the research focus has shifted from chemical to natural preservatives.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current results can be considered as a food hypersensitivity until further clarification is conducted especially because recent literature has suggested that some allergies are due to food additive allergy rather than a true FA. 25 Furthermore, participation was voluntary in the randomly selected schools; thus, parents who had children with a positive FA might have been keener to answer, causing a higher estimate in our population. In terms of statistical analysis, we acknowledge that not adjusting for confounders was a limitation.…”
Section: Discussionmentioning
confidence: 98%
“…In DIATROFI meals, in contrast with the vast majority of commercially available products, no preservative additions are permitted, based on the literature for their potential health risks. For instance, sorbic/benzoic acids and their respective salts, despite their recognition as "safe for consumption for general population within specific limits", have been associated with several health implications, including hypersensitivity/allergenicity effects [30,49] and increased hyperactivity for children [50,51]. Similar health outcomes are reported for other "safe for public consumption" food additives and preservatives [50].…”
Section: Preservatives and Other Additivesmentioning
confidence: 97%
“…For instance, sorbic/benzoic acids and their respective salts, despite their recognition as "safe for consumption for general population within specific limits", have been associated with several health implications, including hypersensitivity/allergenicity effects [30,49] and increased hyperactivity for children [50,51]. Similar health outcomes are reported for other "safe for public consumption" food additives and preservatives [50]. Additionally, among the additives widely used in commercial products for their sensorybased and meal structure properties, glutamic acid, glucuronic acid, and all artificial colors possess plausible health implications [52,53].…”
Section: Preservatives and Other Additivesmentioning
confidence: 99%